Em busca de um tema esquecido: o lugar da educação nas recentes interpretações do Brasil - Marcos Cezar de Freitas; Luciano Mendes de Faria Filho (Araucaria)
This text is proposed to analyze the place reserved for education in the contemporary interpretations of Brazil. To do so, we chose a group of works published from the end of the twentieth century, time when commemorations / discussions about the 500 anniversary of the “Discovery” have been built up until the year 2015 when an Economic Crisis has been installed and resulted in the ousting of the Dilma Roussef from the Republic Presidency. The article defends that, if, throughout the twentieth century, access to education was “Panacea” for all the evils in the country, in the twenty-first century, interpreting Brazil became an exercise that allows us to approach the permanence of those who have got to school, increasing the focus of access for inclusion, aiming to understand more than just overpassing the limits, the approximation, the “doing together” that the almost universalization of the basic school provides. But it also imposes the understanding of the updated and extended distances between the Big house and the Public school on the fostering of class and race privileges, very tradition a land common in Brazil.